Valor biológico de las proteínas contenidas en el producto comercial pulmocare utilizado en terapia nutricional - Rojas Gutiérrez, Flor de María (2015)
ABSTRACT In this research the biological value of proteins Pulmocare commercial product , used in nutritional therapy, using the biological method of net protein utilization ( NPU ) , for it was used Rattus rattus var. norvegicus , of 33-57 days old and 50-60 g in weight. A group aproteic based diet and the other group the food under study was administered , the results were : digestibility 96.45 %, NPU 80.92 % and biological value of 83, 82 %. An analysis of the results it is concluded that every 100 g of Protein Pulmocare commercial product , the body assimilates 84 g.